Stress Urinary Incontinence and Female Sexual Dysfunction: The Role of Pelvic Floor Rehabilitation - Preda, Andreia (2019)
Introduction: The prevalence of urinary incontinence in Portuguese women is 21.4% and has a very negative impact on quality of life including women’s sexual activity. Pelvic floor rehabilitation is the first line treatment used in stress urinary incontinence and may be a tool in the treatment of sexual dysfunction in women with urinary incontinence. The aim of this review is to ascertain whether pelvic floor rehabilitation can improve sexual function in women with stress urinary incontinence.Material and Methods: We reviewed 12 articles in PubMed using the keywords: ‘urinary incontinence’, ‘female sexual dysfunction’ and ‘pelvic floor physical therapy’.Results: Pelvic floor rehabilitation is linked to a decrease in frequency of urinary leakage episodes as well as an improvement of coital incontinence. Furthermore, sexual function evaluation scores post-treatment revealed a positive change. Higher parity, higher adherence to treatment, improvement in the strength of pelvic floor muscles, and a decrease in the frequency of urine leakage were associated with higher improvement in sexual function.Discussion: Sexual function should be considered in the approach of urinary incontinence and standard tools of evaluation are essential tools for clinical assessment and follow-up. More evidence is required to identify the role of pelvic floor rehabilitation in sexual dysfunction of Portuguese women with urinary incontinence.Conclusion: Pelvic floor rehabilitation improves sexual function of women with stress urinary incontinence not only because it decreases the episodes of urine leakage but also because it strengthens pelvic floor muscles.